1999
DOI: 10.1046/j.1365-2362.1999.00441.x
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic destruction of functional proteins by phagocytes in human peritonitis

Abstract: Higher values of extracellularly released phagocyte proteinases concomitant with lower opsonin activity in exudates from patients with persistent peritonitis can be taken as a further hint of the involvement of local proteolysis-induced pathomechanisms in the development of lethal multiple organ failure, which occurred more frequently in patients with persistent peritonitis (54%) than in those with acute peritonitis (27%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
(35 reference statements)
0
1
0
1
Order By: Relevance
“…It has been shown that PMN 11. Rosenthal, J., Thurman, G. W., Cusack, N., Peterson, V. M., elastases are able to induce cellular injury, both in vitro Malech, H. L., and Ambruso, D. R. Neutrophils from patients [10,29] and in vivo [30]. Moreover, elastase-mediated after burn injury express deficiency oxidase components p47-injury occurs in the absence of reactive oxygen metabophox and p67-phox.…”
Section: Cinyl-a-a-p-v-p-nitroanilide Pretreatment With Isopro-mentioning
confidence: 99%
“…It has been shown that PMN 11. Rosenthal, J., Thurman, G. W., Cusack, N., Peterson, V. M., elastases are able to induce cellular injury, both in vitro Malech, H. L., and Ambruso, D. R. Neutrophils from patients [10,29] and in vivo [30]. Moreover, elastase-mediated after burn injury express deficiency oxidase components p47-injury occurs in the absence of reactive oxygen metabophox and p67-phox.…”
Section: Cinyl-a-a-p-v-p-nitroanilide Pretreatment With Isopro-mentioning
confidence: 99%
“…Знижена фагоцитарна активність може бути обумовлена зниженою опсонізуючою активністю крові. Відомо, що при перитоніті виявляється різко знижена опсонізуюча активність крові внаслідок протеолітичної деградації C3 і IgG [14].…”
Section: оригінальні дослідженняunclassified